Нефть Мирного месторождения - Немировская Г. Б. Галина Борисовна; Сечина Т. В. Тамара Владимировна; Кушникова С. Г. Светлана Гурьевна; Смольянинов С. И. Станислав Иванович; Нурмухамедов Р. М. Равиль Мамедович; Нурмухамедова В. К. Валентина Константиновна (Томск, 1989)
Деп. в ЦНИИТЭНефтехим 06.05.89, № 192-НХ-89.